Performance of the MOLES and TFSOM-DIM scores in classifying choroidal nevi and melanoma - David Jahnke; Carsten Grohmann; Bettina Fuisting; Christos Skevas; Martin S. Spitzer; Johannes Birtel (Scientific Reports)
Abstract Choroidal nevi are common benign melanocytic lesions often incidentally found during routine ophthalmic examinations. Patients with choroidal nevi are frequently referred to ocular oncology centers to differentiate these from choroidal melanoma and to exclude a malignant transformation which rarely occurs. However, this causes a high workload for referral centers and may delay diagnosis and treatment of patients with potentially severe conditions. To overcome this, the MOLES score was previously developed which may empower non-specialists to differentiate choroidal nevi from melanoma. In this retrospective study, the performance of the MOLES score was assessed in 695 patients with choroidal nevi and 53 with choroidal melanoma. With a specificity of 96% (choroidal nevi) and a sensitivity of 100% (melanoma) the MOLES score was highly successful in differentiating choroidal nevi from melanoma and may offer great potential to optimize monitoring and referral decisions, and for teleophthalmology applications. Furthermore, the TFSOM-DIM score using risk factors for determining tumor progression was applied and showed a good correlation with MOLES. A complementary use of MOLES and TFSOM-DIM may be beneficial for clinical routine: MOLES for screening by non-experts with limited diagnostic tools and TFSOM-DIM in a referral setting to counsel also regarding potential transformation.